Medication Management Capacity and Its Neurocognitive Correlates in Huntington's Disease. (5th December 2018) - Sumida, Catherine A; Van Etten, Emily J; Lopez, Francesca V; Sheppard, David P; Pirogovsky-Turk, Eva; Corey-Bloom, Jody; Filoteo, J Vincent; Woods, Steven P; Gilbert, Paul E; Schmitter-Edgecombe, Maureen
Abstract: Objective: Although medication management is a necessary daily activity for individuals with Huntington's disease (HD), medication management abilities and their relation to cognitive functioning have not been evaluated. Method: Twenty individuals with HD and 20 healthy adults (HA) completed the Medication Management Abilities Assessment (MMAA). Individuals with HD also completed a self-report medication management measure and neuropsychological tests assessing executive function, retrospective memory, and prospective memory. Results: Individuals with HD performed significantly poorer and made more undertaking errors on the MMAA as compared to HA. No group differences were found in overtaking errors. In the HD group, significant associations were found between undertaking errors and perceived medication management ability as well as between MMAA task performance and measures assessing prospective memory and executive functions. Conclusions: Medication management capacity was negatively affected in individuals with HD and may be associated with difficulty remembering to take medications in the future.